2010
DOI: 10.1089/hum.2009.182
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Serum IgG and Neutralizing Factors Against Adeno-Associated Virus (AAV) Types 1, 2, 5, 6, 8, and 9 in the Healthy Population: Implications for Gene Therapy Using AAV Vectors

Abstract: Adeno-associated viruses (AAVs) are small, nonenveloped single-stranded DNA viruses that require helper viruses to facilitate efficient replication. Despite the presence of humoral responses to the wild-type AAV in humans, AAV remains one of the most promising candidates for therapeutic gene transfer to treat many genetic and acquired diseases. Characterization of the IgG subclass responses to AAV and study of the prevalence of both IgG and neutralizing factors to AAV types 1, 2, 5, 6, 8, and 9 in the human po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
818
8
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 828 publications
(856 citation statements)
references
References 56 publications
29
818
8
1
Order By: Relevance
“…15 These and other similar results strongly support the model that individuals originally infected by AAV2 develop NAbs that cross-react with other AAV serotypes. 10,19 Of the 277 samples assayed, only 2 samples were negative for NAbs against AAV2 but positive for another serotype. (Figure 6) In each of these samples (both from the same patient), low titer antibodies against both AAV5 and AAV8 were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 These and other similar results strongly support the model that individuals originally infected by AAV2 develop NAbs that cross-react with other AAV serotypes. 10,19 Of the 277 samples assayed, only 2 samples were negative for NAbs against AAV2 but positive for another serotype. (Figure 6) In each of these samples (both from the same patient), low titer antibodies against both AAV5 and AAV8 were found.…”
Section: Discussionmentioning
confidence: 99%
“…In approximately 20-60% of this subpopulation, an adaptive humoral response results in the development and maintenance of antibodies capable of neutralizing subsequent infection by AAV2 (neutralizing antibodies (NAbs)). [8][9][10][11][12][13][14][15][16][17][18][19] The existence of NAbs can limit rAAV therapeutic applications that rely on systemic vector administration, for example, by interfering with cell surface binding or promoting reticuloendothelial clearance and destruction of AAV vectors. [20][21][22] Additionally, previous human studies have observed that NAbs against AAV2 cross-neutralize other serotypes of AAV.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Manno et al (44) performed a phase I study of AAV-mediated FIX transgene delivery in patients with hemophilia B, in which one patient with a higher preexisting NAb titer demonstrated lower levels of FIX in the serum than another patient with lower preexisting NAbs against AAV2. These results suggest that preexisting NAbs in the human population can attenuate vector transduction efficiency and inhibit transgene expression upon systemic application (44).In the general human population, over 95% of individuals have been infected by AAV2, with 50% of them having NAbs (3,4,6,10,18,21,24,27,35,48,62,65). The prevalence of NAb in children is lower, ranging from 13 to 25% (9, 35).…”
mentioning
confidence: 99%
“…Although 11 additional types of AAV have been isolated for gene therapy purposes, little to no cross-reactivity of NAbs is demonstrated among these types in animals (27,30,38,60,65). In humans, recent studies have shown that different degrees of NAb cross-reactivity exist between AAV2 and other types (6,10,27,45). There is a lower prevalence of NAbs against AAV1,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation